2015
DOI: 10.1039/c5ib00003c
|View full text |Cite
|
Sign up to set email alerts
|

The lateral diffusion and fibrinogen induced clustering of platelet integrin αIIbβ3reconstituted into physiologically mimetic GUVs

Abstract: Platelet integrin αIIbβ3 is a key mediator of platelet activation and thrombosis. Upon activation αIIbβ3 undergoes significant conformational rearrangement, inducing complex bidirectional signalling and protein recruitment leading to platelet activation. Reconstituted lipid models of the integrin can enhance our understanding of the structural and mechanistic details of αIIbβ3 behaviour away from the complexity of the platelet machinery. Here, a novel method of αIIbβ3 insertion into Giant Unilamellar Vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 58 publications
(142 reference statements)
3
23
0
Order By: Relevance
“…In a recent publication, preferential partitioning of platelet integrin a IIb b 3 into L d domains of phase-separated GUVs has been observed in both inactivated and activated (presence of DTT and Mn 2þ ) states. Fibrinogen binding to activated integrins did not change the preference of the integrin a IIb b 3 heterodimer to L d domains [129]. Moreover, homotypic cell -cell adhesion was modelled by incorporation of epithelial cadherin (E-cadherin) from the cadherin family into protocells and supported lipid bilayers [130,131].…”
Section: Assembly Of Prototissues By Protocell Cross-linking and Adhementioning
confidence: 99%
“…In a recent publication, preferential partitioning of platelet integrin a IIb b 3 into L d domains of phase-separated GUVs has been observed in both inactivated and activated (presence of DTT and Mn 2þ ) states. Fibrinogen binding to activated integrins did not change the preference of the integrin a IIb b 3 heterodimer to L d domains [129]. Moreover, homotypic cell -cell adhesion was modelled by incorporation of epithelial cadherin (E-cadherin) from the cadherin family into protocells and supported lipid bilayers [130,131].…”
Section: Assembly Of Prototissues By Protocell Cross-linking and Adhementioning
confidence: 99%
“…Giant unilamellar vesicles are promising membrane scaffolds for biological investigations, but only few protocols for the incorporation of MPs into GUVs have been described [7][8][9][10]36]. Our results prompted us to test fusion of positively charged SUVs containing MPs, with empty GUVs containing negatively charged lipids.…”
Section: Delivery Of Different Membrane Proteins Into Giant Unilamellmentioning
confidence: 99%
“…Because of these advantages, GUVs are also promising membrane mimetic systems for the design and bottom‐up construction of synthetic cells from purified components . While the insertion of soluble components into the GUV lumen is established , finding general methods for the insertion of functional membrane proteins into the GUV lipid bilayer is an active field of research .…”
mentioning
confidence: 99%
“…With these variations in place, many IMPs have been succesfully inserted and studied in GUVs. These include; Ca 2+ -ATPase and bacteriorhodopsin (143), a flippase from yeast endoplasmic reticulum (149), glycophorin and a K + channel (221,222), and many more (111,143,153,183,185,223). It has also been shown that IMPs and glycosphingolipids retain their natural orientation post electroformation in GUVs produced from native membranes (157).…”
Section: Variations On Existing Methods For Reconstituting Imps Into mentioning
confidence: 99%
“…The formation of GUVs with soluble proteins or nucleic acids in the lumen is well established (158,(180)(181)(182) (146) and this is currently an active research area (118,148,153,(183)(184)(185).…”
Section: Advantages Of Using Guvsmentioning
confidence: 99%